Debate as one of the interactive methods of teaching future aviation specialists to speak English (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
In the given article the advisability of using debate as one of the interactive methods of teaching future aviation specialists to speak English has been proved. Debate can be defined as a broad discussion of moot point to find out different points of view. In the process of research it has been found out that debate promotes students’ cognitive activity activation, personality development of every participant of speech situation, improvement of students’ thinking abilities, decreasing the state of anxiety typical for shy students.Debate is considered to be effective if the following conditions are fulfilled: the right choice of the topic for discussion, it should be interesting for every participant of the debate; active participation of all members; every participant of the debate should have high motivation. Students are highly motivated to discuss real life situations. The techniques of introduction into discussion on the basis of aviation English according to ICAO requirements can be the following: description of real life situation, using the latest news, role play, demonstrating videos, dramatization (modeling the problem situation), audios, asking questions (What? How? Why? What do you know about?).The following stages of conducting debate have been defined: finding out the main problem, dividing it into smaller problems, division of students into groups, explaining the strategy of conducting debate; explaining the rules of conducting debate, recommendations as for data collection; vocabulary exercises (introducing new vocabulary units); preliminary discussion of one of the smaller problems in all groups; brainstorming; applying texts, audios, videos to get the basic information on the given problem. In addition, the discussion list phrase has been introduced for conducting successful debate. Holding debate should include such aspects: the stages of group independent work as for data collection and understanding; announcing the results of work and their discussion in small groups; general discussion and sizing up. The teaching experience proves the fact that debate can be used for teaching students to speak English when they have intermediate and advanced level of English. They are to use a wide range of vocabulary units, grammar constructions, be able to react to phrases of other group members, give arguments to prove their point of view. Debate is not recommended for usage on the initial stage of learning English. Those who want to use this interactive method should take into account the fact that if they want to succeed, they are to do a lot of preliminary work.
Keywords: debate; interactive teaching methods; teaching future aviation specialists to speak English; activation of cognitive and thinking activity; ICAO requirements